2022
DOI: 10.1053/j.gastro.2021.10.037
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Biologic Drugs in Short-Duration Versus Long-Duration Inflammatory Bowel Disease: A Systematic Review and an Individual-Patient Data Meta-Analysis of Randomized Controlled Trials

Abstract: BACKGROUND AND AIMS: Starting biologic treatment early in the course of inflammatory bowel disease (IBD) may be associated with higher efficacy, especially in Crohn's disease (CD). METHODS: This was a systematic review and individual-patient data meta-analysis of all placebo-controlled trials of biologics approved for IBD at study inception (October 2015), using Vivli data-sharing platform. The primary outcome was the proportional biologic/placebo treatment effect on induction of remission in patients with sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 34 publications
2
46
0
1
Order By: Relevance
“…Similarly, registration trials with adalimumab and certolizumab pegol, which stratified according to disease duration showed better responses in patients with shorter disease duration ( Colombel et al., 2007 ; Schreiber et al., 2010 ). A large meta-analysis of 6′168 CD patients, confirmed and extended this observation for other biological therapies, including golimumab and vedolizumab ( Ben-Horin et al., 2021 ). However, the same analyses, failed to show an association between disease duration and response in 3′227 UC patients.…”
Section: Personalizing Choice Of Biologicmentioning
confidence: 71%
“…Similarly, registration trials with adalimumab and certolizumab pegol, which stratified according to disease duration showed better responses in patients with shorter disease duration ( Colombel et al., 2007 ; Schreiber et al., 2010 ). A large meta-analysis of 6′168 CD patients, confirmed and extended this observation for other biological therapies, including golimumab and vedolizumab ( Ben-Horin et al., 2021 ). However, the same analyses, failed to show an association between disease duration and response in 3′227 UC patients.…”
Section: Personalizing Choice Of Biologicmentioning
confidence: 71%
“…Clinical trials have repeatedly demonstrated that early initiation of a biologic therapy either alone or in combination with an immune modulator is superior to immune modulator alone regardless of the biologic chosen. 26,27 However, a question regarding the sequencing F I G U R E 1 A practical approach to incorporating treat-totarget decision making into clinical practice. Modified from Christensen and Rubin.…”
Section: Biologic Therapies As a First Line Treatmentmentioning
confidence: 99%
“…Clinical trials have repeatedly demonstrated that early initiation of a biologic therapy either alone or in combination with an immune modulator is superior to immune modulator alone regardless of the biologic chosen. 26 , 27 However, a question regarding the sequencing of biologics in patients with moderate to severe CD remains. The SEAVUE study, a randomized, double blind, parallel group, active‐controlled phase 3b trial, found that ustekinumab and adalimumab are bot highly effective in treating moderately to‐severely active Crohn's disease in biologically naïve patients.…”
Section: Sequencing Therapies In CDmentioning
confidence: 99%
“…A recent meta-analysis, including individual-patient data from 16 randomized controlled trials (RCT), used the cutoff of 18 months to define short-duration disease, regardless of other characteristics like phenotype or prior treatment. 26 Besides that, some studies have focused on the concept of ‘very early’ CD, again with variable definitions (up to 6 27 or 12 13 , 28 , 29 months since diagnosis). The current definitions of early CD have some main limitations: (i) they mostly rely on the time to a timely diagnosis, what is problematic considering the diagnostic delay that is frequently seen; (ii) inflammation may occur without symptoms; (iii) up to 20% of CD patients have stenosing and penetrating phenotypes without recalling prior symptomatology; and (iv) acute and chronic lesions may coexist, but as soon as irreversible bowel damage is detected, it appears legitimate to consider that the disease is no longer in an early stage.…”
Section: Definition Of Early Diseasementioning
confidence: 99%